Risk factors for maternal outcome in pregnancy complicated with dilated cardiomyopathy - Katsuragi, S; Omoto, A; Kamiya, C; Ueda, K; Sasaki, Y; Yamanaka, K; Neki, R; Yoshimatsu, J; Niwa, K; Ikeda, T (Journal of perinatology, 2012)
Objective: The goal of the study was to determine risk factors for maternal cardiac failure in pregnancy complicated with dilated cardiomyopathy (DCM). Study Design: The subjects were 29 patients diagnosed with DCM before conception or during the first 7 months of pregnancy. DCM was defined as left ventricle end-diastolic dimension (LVDd)⩾48 mm and/or fractional shortening (%FS)⩽30% on echocardiography. Patients were followed until at least 1 year after delivery and were categorized into a poor prognosis group ( n =6; death or end stage heart failure of New York Heart Association (NYHA) class III and IV) and a good prognosis group ( n =23; all other cases). Result: DCM was initially diagnosed during pregnancy in 6/6 and 8/23 patients in the poor and good prognosis groups, respectively ( P <0.005). The %FS of the first test during pregnancy was 17.5±6.2 and 27.4±9.3% in the respective groups ( P <0.005). In eight abortion cases with %FS 15.2±3.1%, %FS, cardiac function and NYHA class were maintained until 20 months after abortion. There was no relationship between LVDd and maternal outcome. Conclusion: Onset during pregnancy and decreased %FS are risk factors for a poor maternal outcome in patients with DCM. Abortion prevents further deterioration of cardiac function in patients with a very low %FS.